His eaudiobook - Dark, Aubrey (Tantor Media, 2015)
I never meant to be here: tied up in bed next to a serial killer. When I followed him home, I was just playing Nancy Drew. Trying to find out his secret. His kiss was intoxicating, and I thought he was harmless. I was wrong. Nancy Drew never ended up in a basement, handcuffed to a radiator, teased to the edge of insanity, begging to be let go. Soon I stopped begging to be let go. Soon I started begging to be his .